Development of Design and Control Manipulator Arm on Hexapod Robot with Smart Vision Sensor - Gralo Yopa Rahmat Pratama; Nuryono Satya Widodo (Universitas Ahmad Dahlan, 2023)
In 2021, the Indonesian Search and Rescue Robot Competition underwent significant changes, transitioning from its original name of